How and when corporate social performance reduces firm risk? The moderating role of corporate governance. (18th May 2022) - Nirino, Niccolò; Battisti, Enrico; Ferraris, Alberto; Dell'Atti, Stefano; Briamonte, Massimiliano Farina
Abstract: This study aims to explore the impact of corporate social performance (CSP) on firm risk, and it proposes the moderating role of corporate governance (CG) among this relationship. Although the literature on corporate social responsibility is extensive, there is still a lack of knowledge about how CSP influences firm risks, as well as the role of CG in this relationship. To fill this gap, we have empirically tested the impact of CSP on a firm's risk through a longitudinal analysis on S&P 500 firms from 2015 to 2019. Results show a significant negative relationship between CSP and firm risks, which is positively moderated by CG mechanisms. Our study contributes to the empirical research on corporate social responsibility and it provides insights for managerial decisions to encourage managers to pursue environmental and social practices that reduce the firm risk, with positive impacts on the firm value.